Pengembangan Permainan Scrabble Kimia sebagai Media Pembelajaran pada Materi Struktur Atom Kelas X SMA/MA - Diana Mustika; Bayharti Bayharti (Universitas Negeri Padang, 2019)
Atomic structure is an abstract topic and contains factual knowledge, conceptual and procedural knowledge. While learning this chapter, students have to exercise more often. The learning media that had developed it this study can be use as exercising media for atomic structure topic. This study used Research and Development type with 4-D model, they are (1) Define, (2) Design, (3) Develop, (4) Disseminate. This research was limited only in third step (Develop) with validity and practicality tests of “Scrabble Kimia” as the final product. Validity test carried out by two chemistry lectures and two chemistry teachers. Practicality test carried out by two chemistry teachers and 29 students of SMAN 1 Batang Anai. This research used quetionaries as research instrument. Data Analyzing was using Kappa Cohen formula. The result of this study indicated that “Scrabble Kimia” for Atomic Structure topic has very high category of validity with 0.82 momen Kappa value. Practicality test showed that this media has very high categories with 0.96 momen Kappa value by teachers and 0.81 momen Kappa value by students. In conclution, the “ Scrabble Kimia” can be used as a learning media for atomic structure topic with very high categories of validity and practicality